Risk reducing surgery with peritoneal staging in BRCA1-2 mutation carriers. A prospective study. Issue 12 (December 2022) - Marchetti, Claudia; Arcieri, Martina; Vertechy, Laura; Ergasti, Raffaella; Russo, Giorgia; Zannoni, Gian Franco; Minucci, Angelo; Ercoli, Alfredo; Scambia, Giovanni; Fagotti, Anna
Abstract: Introduction: International guidelines recommend risk-reducing salpingo-oophorectomy (RRSO) in BRCA1-2 mutations carriers to decrease ovarian cancer occurrence. In this prospective study, we describe the incidence of occult malignancies and the surgical outcomes in asymptomatic BRCA mutation carriers submitted to RRSO. Methods: Data on BRCA1-2 carriers undergoing RRSO with peritoneal washing and peritoneal/omental biopsies (PeS), between January 2019 until March 2021, were prospectively collected. Results: A total of 132 patients were enrolled: 74 BRCA1 and 58 BRCA2 mutation carriers. 31.1% women underwent RRSO and PeS (16.2% of BRCA1 and 50% of BRCA2 carriers), while 68.9% patients were submitted also to concomitant hysterectomy. Almost all the procedures (99.2%) were performed by minimally invasive surgery. Postoperative complications occurred in twelve patients (9.1%): 10 in the concomitant hysterectomy group and two complications in the RRSO group. At the final pathological examination, 6 (4.5%) occult carcinomas were diagnosed: 3 fallopian tube carcinomas, one ovarian carcinoma and two serous tubal intraepithelial carcinomas (STICs), with negative PeS. Median age of occult carcinomas patients at RRSO was 54 (range: 48–79) years. The mean follow up was 20 (range: 7–34) months. During the follow up, no primary peritoneal cancer has been diagnosed. Conclusions: Occult pathologic findings in RRSO occurred in 4.5% (3% invasive carcinomas, STIC 1.5%) among our patients. The routine use of peritoneal biopsies does not improve the detection of occult malignancies. Our data confirm the importance of timely performing RRSO in BRCA1-2 carriers. Highlights: - Risk-reducing salpingo-oophorectomy with mini-invasive surgical approach in BRCA1-2 mutation carriers is a safe procedure. - The routine use of peritoneal biopsies does not improve the detection of occult malignancies. - Adherence to guidelines and to their timetable are essential to further reduce the risk of ovarian cancer.